Managing End-Stage Dementia: Aminoff Suffering Syndrome and Relief of Suffering Units - Aminoff, Bechor Z. (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Aminoff suffering syndrome (ASS) in advanced dementia is the new proposed term for a pathological symptomatology and entity that is characterized by a high Mini Suffering State Examination (MSSE) scale score, <6 months survival, irreversible and intractable aggravation of suffering and medical condition until demise. Dementia is considered a global public health priority. End-stage dementia (ESD) patients are completely helpless, confined to wheelchairs or bedridden, with double incontinence, malnutrition, feeding tubes, decubitus ulcers, and suffering that may continue for months or years. This paper proffers a new, alternative approach and setting for end-stage dementia (ESD) patients with ASS that could pertain to the Israeli setting, and could possibly be applicable in other countries. The MSSE scale comprises 10 items relating to the patients’ characteristics, as well as the perception of their condition by medical staff and families. Each item scores 0 (no) or 1 (yes). Total score ranges between 0-10, with high scores reflecting higher degrees of suffering. Short hospitalization periods of approximately 1 month and treatment in Relief of Suffering Units may be a new, palliative approach and present a possible solution for coping with the horrendous burden of the anguish of end-of-life dementia patients, their families, and the medical and nursing staff.